Kubrador the bet collector - Pareño, Gina.; Jeturian, Jeffrey 1959-. ([Manila] Manufactured and distributed by Paragon Home Video, 2006)
Amelita collects bets for jueteng, an illegal numbers game run by a local network of urban slum dwellers under a gambling lord, who is rumored to be a public official. To earn her daily commissions, Amelita--wife, mother, and grandmother--works and walks thru the neighborhood every day collecting bets and money from regular clients. Faith in God gives her strength and numerology helps her make sense of life?s vicissitudes. She is still haunted by the death of her soldier son who died young. But life remains mysterious and arbitrary. No one can predict when the local police will make a sudden arrest or when another neighbor will meet an untimely death. On All Souls Day, Amelita goes to visit her son?s tomb when suddenly she is caught in another of life?s absurdities. A stray bullet misses Amelita by an inch but hits an innocent bystander instead. Amelita wants to understand why.
Summary taken from container.
Director of photography, Roberto Yn̋iguez ; line producer, Jocelyn Bracamonte ; story and screenplay, Ralston Jover ; story and screenplay supervision, Armando Lao ; sound engineer, Ditoy Aguila ; film editor, Jay Halili ; music, Jerrold Tarog ; production design, Leo Abaya.
Gina Pareño.
Grand Prize 8th Cinema Manila International Film Festival ; Best Film, Best Actress, FIPRESCI Jury Prize Best Film 8th Osian Cine Fan Festival of Asian Cinema ; Best Actress 26th Amiens International Film Festival; Special Jury Prize 7th Asiatica Film Mediale; FIPRESCI Jury Prize Best Film 28th Moscow International Film Festival; Best Actress 33rd Brussels International Independent Film Festival; Special Mention Youth Award 51st Valladolid International Film Festival.